2007
DOI: 10.1590/s1413-70542007000200033
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de fitase em rações de frangos de corte, durante as fases de crescimento e final

Abstract: Os experimentos tiveram como objetivo avaliar os efeitos da enzima fitase nas rações de frangos de corte sobre o desempenho e avaliação de carcaça durante os períodos de crescimento (21 a 35 dias) e final (36 a 45 dias de idade). Duas rações comerciais foram utilizadas, sendo a primeira formulada por uma empresa integradora de frangos de corte (E-1) e a segunda sugerida pela empresa fornecedora da enzima (E-2). Os tratamentos foram: T1 e T4 - ração sem adição da enzima e T2 e T3 - ração com fitase. O delineame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
1
4
1
11
Order By: Relevance
“…However, in addition to the increasing number of broilers produced per year, modern commercial broiler strains present rapid growth, and consequently, diet formulation needs to follow up the changes in their nutritional requirements (Brandão et al, 2007). Phosphorus is nutritionally essential, as evidenced by the different roles it plays in metabolism, and it is particularly important for broiler growth (Assuena et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to the increasing number of broilers produced per year, modern commercial broiler strains present rapid growth, and consequently, diet formulation needs to follow up the changes in their nutritional requirements (Brandão et al, 2007). Phosphorus is nutritionally essential, as evidenced by the different roles it plays in metabolism, and it is particularly important for broiler growth (Assuena et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Working with phytase in diets for broilers, Brandão et al (2007) verified no effect of the enzyme in carcass, breast and abdominal fat yield. However, considering the reduction of the crude protein in the diets, Faria Filho et al (2005) verified that the reduction from 21.5 to 18.5% decreased the breast yield and increased the abdominal fat of the birds at 21 days of age.…”
Section: Resultsmentioning
confidence: 93%
“…The efficiency of phytase enzyme in hydrolyzing mineralphytic-acid complex, leaving them free for absorption and contributing to bone mineralization is evidenced, justifying higher percentages of Ca and P in the treatments with phytase. Oliveira et al (2008), evaluating the tibia bone density in their different areas (middle and distal epiphyseal and diaphyseal), observed that reducing the levels of available phosphorus in diets for broilers also reduces the density of the tibia regions, while the inclusion of phytase in the diet increases the density of different regions, since there were higher phosphorus supplies for bone deposition, demonstrating that the use of this enzyme increases the utilization of the organic phosphorus which is in the form of phytate, reducing the cost of adding inorganic phosphorus to the diet as elucidated by Brandão et al (2007).…”
Section: Resultsmentioning
confidence: 97%
“…Thus, it emphasizes the importance of using best quality feeds and the use of additives that enable broilers to take advantage of the nutrients in feeds (Brandão et al, 2007).…”
Section: Introductionmentioning
confidence: 99%